2019
DOI: 10.17770/etr2019vol1.4162
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cluster Ions and Air Pollution on Human Health

Abstract: Maximum permissible concentration of polluting substances in the atmospheric air is defined in the laws and regulations of many countries. The concentration of cluster ions from 400 to 3000 ions per m3 is generally considered to be appropriate for human health. The author of this article analyses potential cases when air enrichment with air ions could enhance air purification and influence favourably human health. The author also describes possible adverse effects when air ionisation can increase the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…PM10 and PM 2.5 affect the total air ions concentration. It is caused by their common emission sources like vehicular emission, industry, and energy generation (Skromulis, 2019). Skromulis (2019) also reported that relative humidity does not any large or unambiguous impacton AIC directly, while air temperature affects the AIC by increasing it concentration.…”
Section: Introductionmentioning
confidence: 99%
“…PM10 and PM 2.5 affect the total air ions concentration. It is caused by their common emission sources like vehicular emission, industry, and energy generation (Skromulis, 2019). Skromulis (2019) also reported that relative humidity does not any large or unambiguous impacton AIC directly, while air temperature affects the AIC by increasing it concentration.…”
Section: Introductionmentioning
confidence: 99%